Application of electrolyzed water for improving pork meat quality. (October 2017) - Athayde, Dirceu Rodrigues; Flores, Diego Rafael Martins; da Silva, Jéssica Soares; Genro, Ana Luísa Gomes; Silva, Marianna Stafanello; Klein, Bruna; Mello, Renius; Campagnol, Paulo Cezar Bastianello; Wagner, Roger; de Menezes, Cristiano Ragagnin; Barin, Juliano Smanioto; Cichoski, Alexandre José
Abstract: The microbiological and oxidative qualities of pork loin sprayed with different types (slightly acidic, acidic and basic) and combinations of electrolyzed water (EWs) were evaluated. The EWs were applied at two temperatures (18° and 30 °C) and pressures (30 and 45 psi) and the volume corresponded to approximately 10% water commonly used in carcass washing. EW after spraying exhibited a chlorine concentration between 15 and 25 ppm. The application of acidic EW (AEW) alone or in combination with basic EW (BEW) decreased ( P  < 0.05) the microbial counts shortly after spraying. In addition, the combination of BEW + AEW (30 psi) reduced the mesophilic and psychrotrophic bacteria counts throughout the refrigerated storage ( P  < 0.05). The EWs did not increase the lipid oxidation of the samples. On the other hand, a high protein oxidation was observed in the samples sprayed with AEW and slightly acidic EW (SAEW), while BEW was effective to reduce the oxidation reactions. Therefore, the results showed that the combination BEW + AEW may be a viable alternative to reduce the volume of water used at slaughter and to improve the microbiological quality of pork meat. Graphical abstract: Highlights: We applied different combinations of electrolyzed water (EW) in pork meat. EWs did not increase the lipid oxidation of the pork meat. Basic EW protected the samples against protein oxidation. EW is a viable alternative to improve the microbiological quality of pork meat.